An Analysis of Human Resource Competencies and the Implications for MSMe Performance - Halim, Abdul; Pratikto, Heri; Sopia, Sopia (Budapest International Research and Critics University, 2021)
To build and improve the economy of a region or country, the existence of MSMe has a big role and should be taken into account. Behind the success of MSMe is inseparable from the role of HR as business people who are directly involved in planning, developing, and implementing business strategies to improve organizational performance. HR competence is an important thing to be considered by the organization. It covers aspects of knowledge, skills, and abilities. This research focused on analyzing HR competencies and the implications for the performance of Micro, Small, and Medium Enterprises. The research was conducted by collecting several scientific journals, both international journals and national journals that are relevant to the selection of HR competency topics in MSMe. In the initial search, there were 4,546 journals observed, then 6 journals that were considered the most relevant to this topic were selected for review. The results of the research from the six reviewed journals show that HR competence has a positive influence on the performance of MSMe.